Second hand smoke and COPD: lessons from animal studies - Goldklang, Monica P.; Marks, Sarah M.; D'Armiento, Jeanine M. (Frontiers in Physiology, 2013)
Exposure to second hand smoke is a major cause of COPD in the non-smoker. In this review we explore the use of animal smoke exposure models and their insight into disease pathogenesis. The methods of smoke exposure, including exposure delivery systems, are described. Key findings from the acute and chronic smoke exposure models are outlined, including descriptions of the inflammation processes, proteases involved, oxidative stress and apoptosis. Finally, alternatives to rodent models of lung disease are presented.